AI-05 Response gene to complement-32 promotes plasma cell differentiation and enhances lupus-like chronic graft versus host disease. (31st August 2016) - Tatomir, Alexandru; Nguyen, Vinh; Tegla, Cosmin; Cudrici, Cornelia; Badea, Tudor; Rus, Horea; Rus, Violeta
Abstract : Background: Response Gene to Complement (RGC)−32 is an intracellular protein that plays a role in cell growth and promotes cell cycle activation and Akt phosphorylation. RGC-32 is also a downstream target of TGF-β in fibroblasts and renal proximal tubular cells and plays a role in renal fibrogenesis. In immune cells, RGC-32 is expressed by both T and B lymphocytes. Our prior studies showed that RGC-32 promotes Th17 differentiation of mouse CD4 T cells and is highly expressed in human IL-17 CD4 cells. Whether RGC-32 plays a role in the activation and differentiation of B cells and the development of autoimmunity is not known. We used WT and RGC-32 KO mice to determine whether lack of RGC-32 impairs B cell differentiation and activation and alters autoimmune parameters in the chronic graft versus host disease (cGVHD) model of lupus. Materials and methods: B cells were cultured with lps, anti-CD40 mAb, IL-21 and IL-6, IL-4 or TGFβ and RGC-32 mRNA and protein expression was determined. TLR-dependent and T dependent B cell differentiation to plasma cells (PC) was induced with lps and with CD40mAb plus IL-4. cGVHD was induced with 100×10 6 Bm12 splenocytes injected into WT or RGC-32 KO recipients. Host B cell number and activation, anti-dsDNA Ab production, germinal centre (GC) B cell number and proliferation, PC number, expression of transcription factors IRF4 and Blimp1 were assessed at 2 and 4 weeks. Results: RGC-32 mRNA was upregulated in B cells by lps, anti-CD40 mAb, IL-21 and IL-6. RGC-32 KO B cells failed to differentiate normally to PC as demonstrated by a 2-fold reduction in PC numbers generated after lps and anti-CD40+ IL-4 stimulation and impaired upregulation of Prdm1 and IRF4 mRNA. RGC-32 transcripts were upregulated in spleen cells from cGVHD mice and protein expression was detected in B cells and GC cells. RGC-32KO hosts displayed an attenuated autoimmune phenotype as demonstrated by: 1) decreased production of anti-dsDNA autoAb. 2) decreased number and proliferation of GC B cells. 3) decreased number of IgG anti-dsDNA secreting PC and 4) decreased IRF4 and Prdm1 mRNA expression. Conclusions: These results suggest that expression of RGC-32 in B cells is critical for optimal GC proliferation, PC differentiation and autoantibody production in a murine model of lupus. These data support the idea that RGC-32 blockade has the potential to attenuate autoimmune parameters of cGVHD and possibly reverse abnormalities in the T and B cell pathways that contribute to lupus pathogenesis.